Comparison between whole-body vibration, light-emitting diode, and cycling warm-up on high-intensity physical performance during sprint bicycle exercise - Teles, M. C.; Fonseca, I. A. T.; Martins, J. B.; de Carvalho, M. M.; Xavier, M.; Costa, S. J.; de Avelar, N. C. P.; Ribeiro, V. G. C.; Salvador, F. S.; Augusto, L.; Mendonça, V. A.; Lacerda, A. C. R. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to compare the effects of light-emitting diode (LED) irradiation and whole-body vibration (WBV) delivered either in isolation or combination (LED + WBV), warm-up (WU), and a control (C) treatment on performance during a sprint bicycle exercise. Ten cyclists performed a 30-second sprint cycle test under these conditions. The LED light was applied at 4 points bilaterally. Whole-body vibration consisted of 5 minutes of squats associated with WBV. LED + WBV consisted of WBV followed by LED therapy. Warm-up consisted of 17 minutes of moderate-intensity bicycle exercise. Control consisted of 10 minutes at rest. Blood lactate (BL) and ammonia (BA) levels and skin temperature (ST) were determined. Peak power (842 ± 117 vs. 800 ± 106 vs. 809 ± 128 W [p = 0.02 and p = 0.01]), relative power (12.1 ± 1.0 vs. 11.5 ± 0.9 vs. 11.6 ± 1.0 W/kg [p = 0.02 and p = 0.02]), and relative work (277 ± 23 vs. 263 ± 24 vs. 260 ± 23 J/kg [p = 0.02 and p = 0.003]) were higher in the WU group compared with the control and LED groups. In the LED + WBV group, peak (833 ± 115 vs. 800 ± 106 W [p = 0.02]) and relative (11.9 ± 0.9 vs. 11.5 ± 0.9 W/kg [p = 0.02]) power were higher than those in the control group, and relative work (272 ± 22 vs. 260 ± 23 J/kg [p = 0.02]) were improved compared with the LED group. There were no differences for BL, BA, and ST. The findings of this study confirmed the effectiveness of a warm-up as a preparatory activity and demonstrated that LED + WBV and WBV were as effective as WU in improving cyclist performance during a sprint bicycle exercise.